Targeted sequencing of ABCA7 identifies splicing, stop-gain and intronic risk variants for Alzheimer disease. (10th May 2017) - Kunkle, B.W.; Carney, R.M.; Kohli, M.A.; Naj, A.C.; Hamilton-Nelson, K.L.; Whitehead, P.L.; Wang, L.; Lang, R.; Cuccaro, M.L.; Vance, J.M.; Byrd, G.S.; Beecham, G.W.; et al.
Highlights: Sequencing of the Alzheimer disease risk locus ABCA7 is performed. Several Alzheimer's disease risk variants are identified in the gene ABCA7 . Three previously associated ABCA7 variants are confirmed. A 3′-UTR splice variant in ABCA7 is identified as a potential risk variant. Abstract: Several variants in the gene ABCA7 have been identified as potential causal variants for late-onset Alzheimer's disease (LOAD). In order to replicate these findings, and search for novel causal variants, we performed targeted sequencing of this gene in cohorts of non-Hispanic White (NHW) and African-American (AA) LOAD cases and controls. We sequenced the gene ABCA7 in 291 NHW LOAD cases and 103 controls. Variants were prioritized for rare, damaging variants and previously reported variants associated with LOAD, and were follow-up genotyped in 4076 NHW and 1157 AA cases and controls. We confirm three previously associated ABCA7 risk variants and extend two of these associations to other populations, an intronic variant in NHW ( P = 3.0 × 10 −3 ) (originally reported in a Belgian population), and a splice variant originally associated in the Icelandic population, which was significantly associated in the NHW cohort ( P = 1.2 × 10 −6 ) and nominally associated in the AA cohort ( P = 0.017). We also identify a 3′-UTR splice variant that segregates in four siblings of one family and is nominally associated with LOAD ( P = 0.040). Multiple variants in ABCA7 contribute to LOAD risk.